Description of Neosilphitrombium rhipicephalum sp. nov. (Prostigmata: Neothrombiidae) ectoparasite on hard ticks from Iran - Kohansal, Mahnaz; Noei, Javad; Ramroodi, Sara; Rakhshani, Ehsan (Zootaxa, 2024)
An undescribed larva belonging to the family Neothrombiidae was found ectoparasitic on a Rhipicephalus sanguineus (Acari: Ixodida: Ixodidae) by Kohansal et al. (2021). The larva was collected by a sweep net from herbaceous plants in Doroh village, Sarbisheh county, South Khorasan province, Iran. Neosilphitrombium rhipicephalum Noei and Kohansal sp. nov. (Acari: Trombidiformes: Neothrombiidae) is described and illustrated. The generic diagnosis of the genus Neosilphitrombium and key to world genera of Neothrombiidae are amended. Also, an updated key to species of Neosilphitrombium of the world (larva) is presented.